Diagnosis of educational demands and professional deficits of school teachers of the Stavropol territory - L. V. Khalyapina (Вестник Северо-Кавказского федерального университета)
The article emphasizes the necessity of modification in the regional system of advanced training for teachers. The results of the analysis of professional deficits and educational needs of school teachers of the Stavropol Territory are presented. The prerequisites of the implementation of a personalized model of advanced training for teachers are scientifically comprehended.